Manderley in Rebecca by Daphne du Maurier: a haunted house (ACME, 2021)
Manderley, the fictional estate on the Cornish coast resembling Menabilly, where Daphne du Maurier lived and wrote, is at the heart of Rebecca, an enormously successful novel published in 1938 and subsequently adapted by Hitchcock into a 1940 movie. The unnamed female narrator begins by telling us that «Manderley was ours no longer. Manderley was no more». But it is by the power of her vivid imagination that the house rises up before us with its serpentine drive, invaded by monstrous blood-red rhododendrons. Like Charlotte Brontë’s Jane Eyre, Rebecca is a dark and romantic tale of second wives, upper-class husbands, and mysterious British estates concealing secrets. But while Bertha, Rochester’s wife, is still alive, Maxim de Winter’s first wife Rebecca rules Manderley from the kingdom of the dead. In this article I focus on Rebecca as a novel including sentimental, Gothic and crime narratives as well as cross references to the fairy tale and the psychological thriller: all these genres are exploited by Daphne du Maurier, and they contribute to enrich the trope of the haunted house, a powerful and imaginative construction through which du Maurier presents multiple layers of dissonant consciousness and explores the motifs of sexuality and female transgression. She also offers a very peculiar kind of Bildungsroman, in which the shy, self-effacing narrator is willing to find love and happiness. However, in this murder mystery, much is left uncovered, while the natural and the supernatural interact: for this reason, Rebecca can rightly be defined a ghost story. Daphne du Maurier’s imagination, which explores the psyche of each character, represents shocks and traumas, and the readers are invited to look deeper and deeper into the dramatic story until the dénouement, which moves the plot back to the beginning of the novel.